Professional Identity Tensions and Coping Strategies of EFL Pre-Service Teachers - Raharjo, Yohanes Maria Restu Dian; Iswandari, Yuseva Ariyani (JET (Journal of English Teaching), 2019)
Professional identity of English teachers is an important process in which teachers view themselves as a professional based on social views about â€œgood teacherâ€, studentteacher relationship, and self-view as a professional teacher. Teacher preparation program such as Micro Teaching (MT) and Program Pengalaman Lapangan or PreService Teaching Practice (PTP) influences this process by providing support and opportunities in creating a strong professional identity since they are still in a preservice phase. The different nature between MT (situated) and PTP (concrete) can be challenging to the pre-service teachers (PSTs), especially during the PTP. These challenges are called professional identity tensions and they involve PSTs (as a person and professional) and undesirable situation. This study aimed to identify the professional identity tensions faced by EFL PSTs during their PTP and how they coped up with the tensions. The study employed a qualitative survey design. The results identified six professional identity tensions and two coping strategies from the story of seven EFL PSTs. Those PSTs was indicated either to feel tension or to have experiences that might lead them to tension. Keywords: EFL pre-service teacher; professional identity tension; coping strategy